Circulating tumor cell counts/change for outcome prediction in patients with extensive-stage small-cell lung cancer. (March 2016) - Cheng, Ying; Liu, Xiao-Qing; Fan, Yun; Liu, Yun-Peng; Liu, Yi; Liu, Ying; Ma, Li-Xia; Liu, Xian-Hong; Li, Hui; Bao, Hui-Zheng; Liu, Jing-Jing; Zhang, Shuang; et al.
Aims: As data on the use of circulating tumor cells (CTCs) to predict patient outcomes in extensive-stage small-cell lung cancer (ES-SCLC) remain inconclusive, we investigated the clinical value of CTC determination in an open-label, multicenter study of 91 patients with newly diagnosed ES-SCLC.Materials & methods: Blood CTC counts were determined using the CellSearch ® system at baseline, after the second cycle of chemotherapy, and on disease progression.Results & conclusion: Following the second cycle of treatment, CTC numbers and the change in CTCs were strong, significant and independent indicators for both progression-free survival and overall survival in ES-SCLC. The CTC change was associated with both refractory disease (response to initial therapy ≤3 months) and sensitive disease (response to initial therapy >3 months).